Quantitative, Qualitative, Mixed Methods, and Triangulation Research Simplified - Kawar, Lina Najib; Dunbar, Ghada B.; Aquino-Maneja, Emma M.; Flores, Sarah L.; Squier, Victoria Rondez; Failla, Kim Reina (The Journal of continuing education in nursing, 2024)
For the novice nurse researcher, identifying a clinical researchable problem may be simple, but discerning an appropriate research approach may be daunting. What are the differences among quantitative, qualitative, mixed methods, and triangulation research? Which method is applicable for the study one wants to conduct? This article discusses the two main research traditions (quantitative and qualitative) and the differences and similarities in methods for frontline nurses. It simplifies and clarifies how the reader might enhance the rigor of the research study by using mixed methods or triangulation. The four types of research are described, and examples are provided to support readers to plan projects, use the most appropriate method, and effectively communicate findings. [J Contin Educ Nurs. 2024;55(7):338–344.]